2014
DOI: 10.2967/jnumed.113.130674
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Metabolic Response Monitoring During Erlotinib Treatment in Non–Small Cell Lung Cancer

Abstract: The purpose of this study was to prospectively evaluate the timing of metabolic response monitoring with 18 F-FDG PET of (neoadjuvant) erlotinib treatment in patients with early-stage non-small cell lung cancer. Methods: This study was designed as an open-label phase II trial performed in 4 hospitals in The Netherlands. Patients received preoperative erlotinib (150 mg) once daily for 3 wk. Response evaluation was performed after 4-7 d and at 3 wk with 18 F-FDG PET/CT scans. Tumor 18 F-FDG uptake and changes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
(40 reference statements)
1
10
1
Order By: Relevance
“…Consistent with previous reports [3][4][5][6][7][8][9], the results of our study demonstrate that assessment of early FDG-PET response using the EORTC criteria predicts OS in NSCLC patients treated with erlotinib. In our report, the number and timing of FDG-PET scans (at baseline and on days 14 and 56) were in line with the protocol utilized by Mileshkin et al [3].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous reports [3][4][5][6][7][8][9], the results of our study demonstrate that assessment of early FDG-PET response using the EORTC criteria predicts OS in NSCLC patients treated with erlotinib. In our report, the number and timing of FDG-PET scans (at baseline and on days 14 and 56) were in line with the protocol utilized by Mileshkin et al [3].…”
Section: Discussionsupporting
confidence: 93%
“…Because several papers addressing these issues have been published [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], we also performed a retrospective review of our cohort data. The first goal of the retrospective analysis was to investigate whether early FDG-PET assessment of treatment response using TLG-S would be superior to either local assessment with EORTC criteria or hottest-single-lesion assessment with PERCIST criteria for predicting 2-year survival outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that the FDG-PET imagingbased phenotype of response might be an effective early predictor of lung cancer response to TKIs such as erlotinib and gefitinib [35][36][37][38][39][40][41][42][43][44][45]. Recent studies showed that a reduction in FDG tumor uptake observed at 2 days [37,38], 1 week [39], 2 weeks [40,41], and 3 weeks [39,41,42] after treatment with erlotinib or gefitinib, predicts early tumor response as confirmed by CT 4 and 6 weeks later. In contrast, SUVmax has been reported to increase significantly in non-responding patients.…”
Section: Pet Imaging-based Phenotyping Of Targeted Treatment Efficacymentioning
confidence: 88%
“…Tumor heterogeneity on 18 F-FDG-PET/CT for response monitoring in non-small cell lung cancer treated with erlotinib Early response measured with FDG-PET/CT seems to correlate to histopathological response (11). However, there is on ongoing search for reliable parameters to measure response with FDG-PET/CT (12).…”
Section: Commentarymentioning
confidence: 99%